Transmit power minimisation for full-duplex two-way relaying systems with asymmetric packet-rates and quality-of-service requirements - Qian, Chong; Ji, Xiaodong; Cao, Zhanghua; Li, Wenhua (IET communications, 2020)
This study solves the transmit power minimisation problem subject to a target quality-of-service constraint of a full-duplex (FD) two-way decode-and-forward relaying system with asymmetric packet-rates, where the two-way relaying system can operate in two different styles, i.e. half-duplex sources with full-duplex relaying (HDS-FDR) and full-duplex sources with full-duplex relaying (FDS-FDR) styles. For the FDS-FDR style, the relay node can use two strategies to handle the received signals from the sources, namely, physical-layer network coding (PNC) and physical-layer superposition coding (PSC), both of which are referred to as FDS-FDR-PNC and FDS-FDR-PSC styles, respectively. By transforming the transmit power minimisation problem into a two-stage problem, optimum power control (OPC) techniques are developed for the HDS-FDR, FDS-FDR-PNC and FDS-FDR-PSC styles, respectively, giving closed-form solutions for individual transmit power at the relay and the sources. Computer simulations are conducted and the results validate the proposed OPC techniques. It is shown that the FDS-FDR-PNC style performs best in terms of energy saving when the two sources' packet-rates are moderately asymmetric or symmetric. For the case that the packet-rates are strongly asymmetric, the FDS-FDR-PSC style can save more energy than the other two styles.